A molecular and isotopic study of palaeoenvironmental conditions through the middle Cambrian in the Georgina Basin, Central Australia - Pagès, Anais; Schmid, S.; Edwards, D.; Barnes, S.; He, N.; Grice, Kliti (Elsevier BV, 2016)
The Cambrian period marks an important point in Earth's history with profound changes in the ocean's biogeochemistry and the occurrence of the most significant evolutionary event in the history of life, the Cambrian explosion. The Cambrian explosion is described as a succession of complex cycles of extinctions and radiations. This study integrates biomarkers and their compound-specific stable carbon isotopes to investigate the palaeoenvironmental depositional conditions in middle Cambrian (Series 3) sedimentary rocks (Thorntonia Limestone, Inca Formation and Currant Bush Limestone) from two drillholes in the Undilla Sub-basin in the eastern Georgina Basin, central Australia. The occurrence of photic zone euxinia (PZE) was detected throughout these three formations by the identification of green sulfur bacteria Chlorobiaceae-derived biomarkers, including a series of 2,3,6-aryl isoprenoids and the intact biomarker isorenieratane. Pulses of enhanced PZE conditions were detected in two core intervals (90-110 mKB, Currant Bush Limestone and 170-200 mKB, Inca Formation) by an increase in the 2,3,6-aryl isoprenoids and C19 biphenyl concentrations. These enhanced PZE conditions were followed by blooms of phytoplankton, as demonstrated by the increase in algal-derived biomarker (i.e. pristane, phytane and the C19 n-alkane) concentrations and compound-specific isotopes. These observations confirm that palaeoenvironmental conditions were similar to those reported for the Permian/Triassic and Triassic/Jurassic mass extinction events. The sterane distributions varied across the three formations reflecting possible changes in the phytoplanktonic communities through time. Although a rise in atmospheric oxygen during the Cambrian has been previously associated with the rapid evolution of metazoans, the ecological challenges related to widespread anoxia must have had a major influence on the evolution of life in Cambrian oceans.